Psychosocial profile of perpetrators adolescents through mobile phone and internet - B. Iranzo; J. Ortega-Barón; I. Carrascosa; A. J. Clemente (INFAD, 2019)
This study’s main objective is to analyze the psychosocial profile of adolescent perpetrators of cyberbullying, taking into account the following indicators of psychosocial adjustment: satisfaction with life,  non-conformist reputation and antisocial behavior inside and outside the school context. The sample consisted of 896 Spanish students (49.7% boys and 50.3% girls), aged between 11 and 19 years (M = 13.9, ST = 1.5). There are significant differences between the cyberbullies groups and non-perpetrators adolescents; the severe cyberbullies, followed by occasional cyberbullies, show the most controversial psychosocial adjustment in all the variables analyzed, and teens -perpetrators adolescents show more tailored psychosocial adjustment. These results provide relevant information on the importance of psychosocial adjustment in the prevention and intervention of cyberbullying.